Contributors and potential solutions to professional burnout amongst dental surgeons of Islamabad: A mixed method study - Masoud, Saba; Anbreen Aziz; Sheze Haroon Qazi; Hajra Shahid; Rubina Mumtaz (Journal of the Pakistan Medical Association, 2025)
Objective: To assess professional burnout among dentists in an urban setting. of Islamabad using Maslach Burnout Inventory, alongside conducting their semi structured interviews to investigate the contributors and potential management strategies over a period of six months. Method: The observational, mixed method study was conducted at a tertiary care teaching hospital in Islamabad, Pakistan, from January to June 2024, and comprised fulltime faculty members from all private dental teaching hospitals in the city having a minimum of three years of professional experience. Maslach Burnout Inventory, comprising emotional exhaustion, depersonalization and personal accomplishment components, was shared online with the subjects. Subsequently, semi-structured interviews were conducted with those who were filtered to be burntout cases. Qualitative data was subjected to thematic analysis. Results: Of the 36 subjects, 8(22.2%) with age ranging 31-55 years were found to be burnout cases in two out of three categories; 6(75%) females and 2(25%) males. All the 8(100%) subjects were involved in both clinical and academic pursuits. Qualitative data led to the emergence of 8 major themes; excessive workload, weak employee-employer relationship, lack of resources, lack of monetary benefits, lack of acknowledgement, disturbed work-life balance, administrative issues, and pressure to deliver. Conclusion: Healthcare institutions should strive to provide a supportive and sustainable environment for professionals, and implement interventions that may enhance their wellbeing. This will ultimately improve work efficiency. Key Words: Professional burnout, Qualitative research, Maslach burnout inventory, Emotional exhaustion, Depersonalisation.